Les guérillères - Wittig, Monique (University of Illinois Press, 2007)
"One of the most widely read feminist texts of the twentieth century, and Monique Wittig's most popular novel, Les Guerilleres imagines the attack on the language and bodies of men by a tribe of warrior women. Among the women's most powerful weapons is laughter, but they also threaten literary and linguistic customs of the patriarchal order with bullets. In this novel first published in 1969, Wittig animates a lesbian society that invites all women to join their fight, their circle, and their community. A pathbreaking novel about creating and sustaining freedom, the book derives much of its energy from its vaunting of the female body as a resource for literary invention."--BOOK JACKET.